2020
DOI: 10.1007/s00234-019-02335-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain miliary enhancement

Abstract: Purpose Miliary enhancement refers to the presence of multiple small, monomorphic, enhancing foci on T1-weighted postcontrast MRI images. In the absence of a clear clinical presentation, a broad differential diagnosis may result in invasive procedures and possibly brain biopsy for diagnostic purposes. Methods An extensive review of the literature is provided for diseases that may present with miliary enhancement on T1weighted brain MR images. Additional disease-specific findings, both clinical and radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 79 publications
(196 reference statements)
0
15
0
1
Order By: Relevance
“…Хронические очаги, в свою очередь, могут иметь пониженный МР-сигнал в режиме Т1-ВИ и пониженный с ободком повышенного в режиме Т2-FLAIR, что отражает их кистозную перестройку. При синдроме Сусака в литературе описаны случаи феномена лептоменингеального контрастирования, наличие которого также обсуждается при прогрессирующих формах РС [23][24][25].…”
Section: клинический пример 4 синдром сусакаunclassified
“…Хронические очаги, в свою очередь, могут иметь пониженный МР-сигнал в режиме Т1-ВИ и пониженный с ободком повышенного в режиме Т2-FLAIR, что отражает их кистозную перестройку. При синдроме Сусака в литературе описаны случаи феномена лептоменингеального контрастирования, наличие которого также обсуждается при прогрессирующих формах РС [23][24][25].…”
Section: клинический пример 4 синдром сусакаunclassified
“…Vascular-associated diseases as well as inflammatory and neoplastic processes may exhibit an angiocentric lesion pattern on T2 WI due to the anatomically predetermined propagation along the PVS, which is illustrated by taking into account the T1 WI after contrast application (pc T1 WI) [39,[66][67][68][69]. In addition to sarcoidosis (see ▶ Fig.…”
Section: Angiocentric Propagation Patternmentioning
confidence: 99%
“…4 Even when miliary brain lesions are detected by MRI, the appropriate treatment can be delayed, as miliary brain lesions represent a broad differential diagnosis, including infectious, inflammatory and nutritional aetiologies. 13 Much of the current understanding of MiM is based on postmortem pathological examination. Ogawa et al 3 found that MiM is localised within the perivascular (Virchow-Robin) space with extension into the subpial space without invasion of the brain parenchyma, consistent with prior reports.…”
Section: Mainmentioning
confidence: 99%
“… 4 Even when miliary brain lesions are detected by MRI, the appropriate treatment can be delayed, as miliary brain lesions represent a broad differential diagnosis, including infectious, inflammatory and nutritional aetiologies. 13 …”
Section: Mainmentioning
confidence: 99%